2023
DOI: 10.3390/cancers15143707
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lymph Node Tumor Burden in Node-Positive Prostate Cancer Patients after Robotic-Assisted Radical Prostatectomy with Extended Pelvic Lymph Node Dissection

Abstract: Background: Prostate cancer (PCa) nodal staging does not account for lymph node (LN) tumor burden. The LN anatomical compartment involved with the tumor or the quantified extent of extranodal extension (ENE) have not yet been studied in relation to biochemical recurrence-free survival (BRFS). Methods: Histopathological slides of 66 pN1 PCa patients who underwent extended pelvic lymph node dissection were reviewed. We recorded metrics to quantify LN tumor burden. We also characterized the LN anatomical compartm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Regarding discordant lesions in the lymph nodes, recent studies, such as the study by Gottlieb et al ( 30 ), revealed that histopathologically, the tumor burden in lymph node lesions is associated with BCR-free survival time in PCa patients. Furthermore, Schwartz et al ( 31 ) described that the stratification of lymph node lesions based on size and the anatomical region can hinder the serial follow-up of the lesions and potentially provide discordant findings in their classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding discordant lesions in the lymph nodes, recent studies, such as the study by Gottlieb et al ( 30 ), revealed that histopathologically, the tumor burden in lymph node lesions is associated with BCR-free survival time in PCa patients. Furthermore, Schwartz et al ( 31 ) described that the stratification of lymph node lesions based on size and the anatomical region can hinder the serial follow-up of the lesions and potentially provide discordant findings in their classification.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they determined that an optimal SUVmax threshold of 8.3 could be applied to identify PCa lesions through [ 18 F]PSMA-1007 PET/CT. Regarding discordant lesions in the lymph nodes, recent studies, such as the study by Gottlieb et al (30), revealed that histopathologically, the tumor burden in lymph node lesions is associated with BCR-free survival time in PCa patients. Furthermore, Schwartz et al (31) described that the stratification of lymph node (31) reported that when only the short axis of the lymph node lesion is considered, there is a better and more significant correlation with the tumor burden, and they recommend adopting the measurement of the short-axis diameter for lymph node lesions in radiological practice.…”
Section: Discussionmentioning
confidence: 99%